Pullusurfactans A–E, new biosurfactants produced by Aureobasidium pullulans A11211-4-57 from a fleabane, Erigeron annus (L.) pers. (November 2018) - Kim, Jong-Shik; Lee, In-Kyoung; Yun, Bong-Sik
Abstract Yeast biosurfactants have potent applications in medical, cosmeceutical, and food industries due to their specific modes of action, low toxicity, and applicability. In this study, biosurfactant-producing yeasts were screened for various industrial applications. Among them, Aureobasidium pullulans strain A11211-4-57 with potent surfactant activity from fleabane flower, Erigeron annus (L.) pers., was selected. From culture supernatant of strain A11211-4-57, five new low-surface-tension chemicals designated as pullusurfactans A–E were identified through consecutive chromatography steps, involving ODS, silica gel, Sephadex LH-20, and ODS Sep-pak cartridge columns. Based on mass and NMR measurements, structures of pullusurfactans A–E were determined asmyo -inositol lipids with molecular formulae of C20 H35 O9, C18 H32 O8, C20 H35 O9, C24 H42 O9, and C18 H32 O8, respectively. These compounds exhibited potent biosurfactant activities (22.90, 22.40, 32.28, 25.28, and 22.44 mN/m, respectively). These results suggest that these novel biosurfactants have potential use as biosurfactants in industrial aspect.